A Case Report on Gastroduodenal Strongyloidiasis Causing Protein Losing Enteropathy - S. Bharti; A. Singh; R. Kirti; . Navneet (New Horizons in Medicine and Medical Research Vol. 5, 2022)
Strongyloidiasis is a widespread illness with a complicated life cycle that infects humans percutaneously. We discuss the case of a 46-year-old lady who arrived with abdominal pain and distention. She was on PPI for recurrent gastritis. She also discusses her steroid use for joint pain. A USG of the abdomen revealed significant ascites. Endoscopy of the upper gastrointestinal tract revealed diffuse erythematous gastric mucosa with a mild mosaic pattern, as well as edematous duodenal mucosa with patchy erythema. Strongyloides stercoralis was found to be infested in the stomach mucosal glands during histopathological investigation of a gastric sample. After a course of antihelmintic medication, the patient was entirely recovered. This is a case report of gastroduodenal strongyloidiasis with presenting symptom of abdominal pain and ascites.